Vesicular Nucleo-Cytoplasmic Transport—Herpesviruses as Pioneers in Cell Biology - Thomas C. Mettenleiter (Viruses, 2016)
Herpesviruses use a vesicle-mediated transfer of intranuclearly assembled nucleocapsids through the nuclear envelope (NE) for final maturation in the cytoplasm. The molecular basis for this novel vesicular nucleo-cytoplasmic transport is beginning to be elucidated in detail. The heterodimeric viral nuclear egress complex (NEC), conserved within the classical herpesviruses, mediates vesicle formation from the inner nuclear membrane (INM) by polymerization into a hexagonal lattice followed by fusion of the vesicle membrane with the outer nuclear membrane (ONM). Mechanisms of capsid inclusion as well as vesicle-membrane fusion, however, are largely unclear. Interestingly, a similar transport mechanism through the NE has been demonstrated in nuclear export of large ribonucleoprotein complexes during Drosophila neuromuscular junction formation, indicating a widespread presence of a novel concept of cellular nucleo-cytoplasmic transport.